PEMETAAN KEMAMPUAN GURU SEKOLAH DASAR DALAM MEMAHAMI KURIKULUM 2013 - Nana Hendracipta (JPsd (Jurnal Pendidikan Sekolah Dasar), 2015)
Curriculum implementation in 2013 requires socialization, socialization efforts have been made by the government through training, but still a little research that describes the ability of teachers to understand the curriculum  2013. Therefore, this study was conducted in order to describe the ability of elementary school teachers in understanding the curriculum  2013. The purpose of this research are: (1). To describe the elementary school teachers' understanding of the curriculum as the city of Tangerang, 2013. (2). To illustrate the successful implementation of the curriculum socialization. The samples were taken from elementary school teachers throughout the city of Tangerang with simple random sampling technique. The method used is descriptive survey techniques. Analysis of the data using a simple percentage, then categorized. Based on the research results can be summarized as follows: 30% of respondents have an understanding of the category of "Very Good", while those in the category of "Good" as much as 60%, which is in the category "Self" as much as 6% and the category of "Less" by 5 %. Keywords : Curriculum Implementation, Curriculum 2013